Identities of some names in Gomphrena (Amaranthaceae) - Sandoval-Ortega, Manuel Higinio; Zumaya-Mendoza, Silvia (Phytotaxa, 2023)
The typification of names Gomphrena decumbens var. nana, G. filaginoides, G. nitida, and G. pringlei are discussed. Specimens from P, GH, US, and Z are designated as lectotypes. The identity of the name Gomphrena globosa var. albiflora is discussed reaching to the conclusion that it is a synonym of G. palmeri.